2015
DOI: 10.1007/s10068-015-0041-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hyperglycemic and hypolipidemic effects of baechukimchi with Ecklonia cava in type 2 diabetic db/db mice

Abstract: Anti-hyperglycemic and hypolipidemic effects of baechukimchi with Ecklonia cava were investigated in type 2 diabetic db/db mice. Baechukimchi with 15% added E. cava (BKE) was fermented at 5 o C for 28 days to obtain optimally ripened BKE (pH 4.28, acidity 0.71). BKE was subjected to extraction using 80% methanol. Male db/db mice were divided into groups of db/db-control, db/db-BKE, and db/db-rosiglitazone (db/db-RG). Compounds were orally administered every day for 6 weeks. The db/ db-BKE mice had lowered bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The data on glycogen were displayed in Table ( 5), where a significant increase was seen in the standard group. These results were in agreement with those of Lee et al (2015) who discovered that after the study period, the body weight of rat in the positive control group was considerably (p<0.05) higher than that of rat in the diabetic group. There was a significant increase in body weight by 37.96% in the standard group(C), In comparison, it increased by 13.41% in the group taking methanolic extract from Sargussium sp 150mg/kg algae to 15.03% in the group taking an water extract from Laurencia Papillose 150mg/kg algae.…”
Section: Effect Of the Tested Extracts Algae On Serum Enzymes Activit...supporting
confidence: 93%
“…The data on glycogen were displayed in Table ( 5), where a significant increase was seen in the standard group. These results were in agreement with those of Lee et al (2015) who discovered that after the study period, the body weight of rat in the positive control group was considerably (p<0.05) higher than that of rat in the diabetic group. There was a significant increase in body weight by 37.96% in the standard group(C), In comparison, it increased by 13.41% in the group taking methanolic extract from Sargussium sp 150mg/kg algae to 15.03% in the group taking an water extract from Laurencia Papillose 150mg/kg algae.…”
Section: Effect Of the Tested Extracts Algae On Serum Enzymes Activit...supporting
confidence: 93%
“…The weights of the liver and kidney tissues in the DC group were higher than those in the NC group, but tended to decrease following the intake of the AG group. Polydipsia, polyuria, and polyphagia are typical symptoms observed in diabetes (32). Yamanaka et al (33) reported that treatment with rosiglitazone increased the body weight of db/db mice.…”
Section: Resultsmentioning
confidence: 99%